2017
DOI: 10.18203/2320-6012.ijrms20171252
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of outcome in newborns with respiratory distress in Osogbo, Nigeria

Abstract: INTRODUCTIONRespiratory distress is one of the commonest presentations necessitating hospital admission of newborns.1 About 15% of term infants and 29% of late preterm infants admitted to the neonatal intensive care unit develop have significant respiratory symptoms; this is even higher for infants born before 34 weeks' gestation.2,3 The clinical presentations of respiratory distress in the newborn include difficulty with breathing (nasal flaring, recessions or retractions in the intercostal, subcostal, or sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 9 publications
(25 reference statements)
0
12
1
1
Order By: Relevance
“…Adebami et al found respiratory distress due to congenital heart disease in 6.1% of the study participants. 17 In our study, congenital heart disease was the cause for respiratory distress in 6.4% of neonates.…”
Section: Scenario Of Neonatal Respiratory Distressmentioning
confidence: 57%
“…Adebami et al found respiratory distress due to congenital heart disease in 6.1% of the study participants. 17 In our study, congenital heart disease was the cause for respiratory distress in 6.4% of neonates.…”
Section: Scenario Of Neonatal Respiratory Distressmentioning
confidence: 57%
“…Higher mortality rate accompanied higher incidence of RDS, MAS, and pneumonia while higher survival rate with increased incidence of TTN. During the period of the study, the case fatality rate was (38.9%) [32,35]. Many variables had a great effect on the outcome of our studied cases as had an odds ratio >1 like male gender, RDS, CDH, pneumonia, apnea, tachypnea >60/min, cyanosis and irritability where apnea had the highest odd ratio of clinical signs.…”
Section: Discussionmentioning
confidence: 83%
“…The most accepted diagnosis for NRD was based on the clinical presence of at least one or two of the elements of the following three signs: an abnormal respiratory rate ( tachypnoea [respiratory rate above 60 breaths/minute], bradypnoea [respiratory rate less than 30 breaths/minutes], respiratory pauses [an absence of breathing movements for a period less than 20 seconds] and apnoea [an absence of breathing movements for a period greater than 20 seconds]), signs of laboured breathing (expiratory grunting, nasal aring, intercostal recessions, xiphoid recession and thoraco-abdominal asynchrony) and generalised or localised cyanosis (1,3,4,8,16,19,21,25,27,(31)(32)(33)35,53,(63)(64)(65). The rest of the clinical examination is aimed at investigating the aetiology of NRD.…”
Section: Discussionmentioning
confidence: 99%